Implementation of Web-Based Client Outreach Activity Data Processing Systems at Bina Muda Gemilang Foundation - Sri Rahayu; Po Abas Sunarya; Salsabillah Devia Khansa (Universitas Raharja, 2021)
In the current era where technology is increasingly developing so that it can change a pattern or habit of society, it can be used by anyone, anywhere. The Bina Muda Gemilang Foundation is no exception, which also takes advantage of technological developments to increase the efficiency and effectiveness of existing business processes. One of the business processes that run at this foundation, namely the data processing of client outreach activities, there are still many gaps where the error rate of data input is quite high. Also frequent date falsification of outreach activities and officer indiscipline in data input. This study aims to solve existing problems by creating a web-based system that is made using the programming languages PHP and MySQL for the database, which can facilitate business processes and minimize errors.